Physical Activity, Sedentary Behavior, and Satisfaction With Life of University Students in Qatar: Changes During Confinement Due to the COVID-19 Pandemic - Hermassi, Souhail; Hayes, Lawrence D.; Salman, Ahmad; Sanal-Hayes, Nilihan E. M.; Abassi, Emna; Al-Kuwari, Lolwa; Aldous, Nada; Musa, Nemah; Alyafei, Amna; Bouhafs, El Ghali; Schwesig, René (Frontiers in Psychology, 2021)
This study explored the effects of home confinement on physical activity (PA) and satisfaction with life (SL) among university students during the COVID-19 pandemic. A total of 531 subjects participated [male: n=203; female: n=328; age: 33.1±5.2years; mass: 72.1±17.5kg; height: 1.67±0.12m; and body mass index (BMI): 25.7±5.06 kg/m2]. Online survey questions considered “before” and “during” confinement. Confinement reduced all PA intensities (ηp2=0.09–0.45, p<0.001) and increased daily sitting time (ηp2=0.58, p<0.001). The largest reduction was in moderate intensity PA [metabolic equivalent of task-minutes/week (MET), ηp2=0.45, p<0.001]. SQL decreased, with the score for “I am satisfied with my life” (ηp2=0.42, p<0.001) decreasing from 28.4±5.7 to 20.6±9.7 arbitrary units (AU). Concerning SL, the largest change was detected for “the conditions of my life are excellent” (ηp2=0.54, p<0.001). Time changes in all variables were demonstrative of large negative changes in both sexes. The difference in change between sexes was largest in terms of magnitude for the variable “the conditions of my life are excellent” (difference between groups, Δd=0.98). In sum, COVID-19 confinement reduced PA, heightened sitting time, and reduced SL in Qatar University students. This investigation could have a significant impact in developing PA guidelines for health maintainance during COVID-19 and successive pandemics in university students.